4 Stat. at Large of S.C. 34 (1838) - (:unkn) unknown (My University, 1756)
An Act for Disposing of the Acadians Now in Charleston, § 10: Prohibited “Acadians” from using a firearm or other offensive weapon and allowed people to seize such weapons.
Keywords: ENSLAVED PERSONS & OTHER MINORITIES